A ROAD SAFETY EVALUATION MODEL IN THE CONTEXT OF LEGISLATIVE CHANGES - Anna BORUCKA; Grzegorz SOBECKI (Transport Problems)
Road accidents are affected by various factors, but many of them are not monitored and collected, and some of them are not even known. Important factors that are often overlooked in research are legislative issues and legal changes regulating road safety, which are the subject of the study in this article. As it is extremely difficult to prove a significant influence of these factors and, therefore, to demonstrate that the impact of legislative changes on the number of road accidents is significant, this variable was considered while analyzing the impact of other variables, which, in the authors' opinion, were the most important and, above all, known over the period in question. Day of the week, month, and year are selected. It was decided that other factors influencing the decreasing number of accidents would be included in the trend. With this assumption, the analysis of an additional variable that marks the periods of changes in legal regulations and the confirmation of its significant impact on the number of accidents will allow us to conclude that it is an important element shaping road safety.